Gaming Preferences and Personality among School Students - Balan Rathakrishnan; Soon Singh Bikar Singh; Azizi Yahaya (Children, 2023)
Gaming has vastly developed into numerous genres; nonetheless, most studies in the literature emphasize the violent genre only. Therefore, this study was conducted to investigate the relationship between personality and gaming preferences among school students. This study also aims to investigate the difference in the time spent on gaming based on gender. The third objective involves examining the differences in frequency in playing a video game based on age. The sample group comprised 420 school students aged between 12 and 17 years old, including hardcore and casual gamers. The online survey was conducted using Google Forms, and the participants were requested to answer the demographic questionnaire, Big Five Inventory, and Gaming Preferences Questionnaire. The obtained data were analyzed using SPSS 26.0 software for general descriptive statistics. The results show that there was a significant relationship between gaming preferences role-playing game (RPG), combat, online, and music genres) and personality (extraversion, agreeableness, conscientious, neuroticism, and openness). The results also indicate a difference between gender and the number of hours spent on gaming, but no such difference existed between age and the frequency of playing games. From the psychological perspective, gaming preference is related to their personality and influences the behavior of children and overall health in daily life.